Acute interstitial nephritis, a potential predictor of response to immune checkpoint inhibitors in renal cell carcinoma - Raquibul Hannan; Alana Christie; Payal Kapur; James Brugarolas; Hans Hammers; Viral Patel; Roy Elias; Joseph Formella; William Schwartzman; Qi Cai; Venkat Malladi; Miguel Vazquez; et al. (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitors (ICIs) such as nivolumab and ipilimumab have improved outcomes in metastatic renal cell carcinoma (mRCC) patients, but they are also associated with immune-related adverse events (irAEs). As observed in melanoma, we hypothesized that patients experiencing an autoimmune reaction directed against the tissue of origin may be more likely to benefit from ICI. Specifically, we asked whether patients with immune-related acute interstitial nephritis (irAIN) exhibited improved outcomes. Using Kidney Cancer Explorer (KCE), a data portal and i2b2-based central database for clinical, pathological and experimental genetic data, we systematically identified all patients with mRCC at UT Southwestern Medical Center (UTSW) from 2014–2018 who received at least one dose of ICI. More recent cases were identified through a provider query. We extracted creatinine (Cr) values at baseline and over the entirety of each patient ICI treatment course using KCE. Patients with ≥ 1.5-fold Cr increase over baseline were investigated. The likelihood of irAIN was determined based on the work-up (biopsy, if available), or by clinical criteria (timing of kidney injury, exclusion of other etiologies, treatment with immunosuppressants and response). We identified 177 mRCC patients who received at least one dose of ICI, 36 of whom had ≥ 1.5-fold increase in Cr over baseline while on treatment. Of those, two had biopsy-proven irAIN and one was clinically diagnosed, resulting in an incidence of 1.7%. One additional biopsy-proven case past 2018 was identified through a provider query, for a total of four patients. Two received combination nivolumab and ipilimumab in the first line, whereas the remaining received nivolumab after first line therapy. irAIN onset ranged from 1.5 to 12 months. All four patients stopped ICI with recovery of renal function, at least partially, three after receiving systemic steroids. Notably, all four patients had a deep response. In conclusion, irAIN is a rare event, but it may portend a higher likelihood of response. One possible explanation is antigenic overlap between normal renal tubular cells and tumor cells.